Safer alternatives? Bisphenol F and Bisphenol S induce oxidative stress in Drosophila melanogaster larvae and trigger developmental damage. (May 2023) - Santos Musachio, Elize A.; Poetini, Marcia Rósula; Janner, Dieniffer Espinosa; Fernandes, Eliana Jardim; Meichtry, Luana Barreto; Mustafa Dahleh, Mustafa Munir; Guerra, Gustavo Petri; Prigol, Marina
Abstract: Bisphenol F (BPF) and Bisphenol S (BPS) are safe alternatives substances? Here Drosophila melanogaster were exposed during development (larval stage) to BPF and BPS (0.25, 0.5 and 1 mM). Upon reaching the last larval stage (3rd stage), markers of oxidative stress and metabolism of both substances were evaluated, along with investigation of mitochondrial and cell viability. This study is attributed to an unprecedented fact: BPF and BPS exposed larvae, both at concentrations of 0.5 and 1 mM, showed higher cytochrome P-450 (CYP450) activity. The GST activity increased in all BPF and BPS concentrations, and reactive species, lipid peroxidation, superoxide dismutase, and catalase activity increased in larvae (BPF and BPS; 0.5, and 1 mM); nonetheless, mitochondrial and cell viability decreased with 1 mM of BPF and BPS. In addition, the reduced number of pupae formed in the 1 mM BPF and BPS groups and melanotic mass formation may be attributed to oxidative stress. From the pupae formed, the hatching rate reduced in the 0.5 and 1 mM BPF and BPS groups. Thus, the possible presence of toxic metabolites may be related to the larval oxidative stress condition, which is detrimental to the complete development of Drosophila melanogaster .